Effect of aspirin in preventing deep vein thrombosis (DVT) after lumbar canal spinal stenosis surgeries: a double-blind parallel randomized clinical trial. Issue 6 (8th November 2022) - Nikouei, Farshad; Chehrassan, Mohammadreza; Shakeri, Mohammadreza; Mahdavi, Seyed Mani; Ameri, Ebrahim; Eslami, Arvin; Habibollahzadeh, Ali; Ghandhari, Hasan
Abstract : Background: Deep vein thrombosis (DVT) is a great postoperative challenge in all orthopaedic surgeries. To the authors' knowledge, this study is the first to evaluate the efficacy of aspirin administration in the prevention of DVT in patients undergoing lumbar spinal surgery. Methods: In this double-blind parallel randomized clinical trial, a total of 126 candidates (age 40 yr and older) were admitted between June 2021 to December 2021. Patients were randomly assigned to the intervention chemoprophylaxis group (41 patients receiving 325 mg aspirin) and controls. The DVT occurrence was recorded by clinical features (Well's criteria), Doppler lower limbs ultrasound, and D-dimer levels in all participants at baseline (24 hr before the time of surgery) and 2, 6, and 12 wk after surgery in postoperative visits. Results: The mean age of the participants was 63.72±6.87 yr. Baseline demographic values were similar in both groups ( P >0.05). The mean follow-up duration was 6.11±2.33 mo. No cases of DVT or abnormal findings on Doppler ultrasound were observed in either group. The mean duration of hospitalization or intensive care unit (ICU) admission was similar between the two groups. Mean baseline D-dimer levels were significantly higher in the intervention group compared with the controls ( P =0.047), while it was similar in both groups 3 mo after the operation ( P =0.13). Conclusions: In the current study, no case of DVT was observed in either study group. These data do not support the use of aspirin as an anticoagulant for DVT prophylaxis following regular lumbar spinal surgeries. Level of Evidence: Level II.